Deep Sequencing Reveals Occurrence of Subclonal ALK Mutations in Neuroblastoma at Diagnosis - Angela Bellini; Virginie Bernard; Quentin Leroy; Thomas Rio Frio; Gaëlle Pierron; Valérie Combaret; Eve Lapouble; Nathalie Clément; Hervé Rubie; Estelle Thébaud; Pascal Chastagner; Anne Sophie Defachelles; et al. (2015)
Abstract Purpose: In neuroblastoma, activating ALK receptor tyrosine kinase point mutations play a major role in oncogenesis. We explored the potential occurrence of ALK mutations at a subclonal level using targeted deep sequencing. Experimental Design: In a clinically representative series of 276 diagnostic neuroblastoma samples, exons 23 and 25 of the ALK gene, containing the F1174 and R1275 mutation hotspots, respectively, were resequenced with an extremely high depth of coverage. Results: At the F1174 hotspot (exon 23), mutations were observed in 15 of 277 samples (range of fraction of mutated allele per sample: 0.562%–40.409%). At the R1275 hotspot (exon 25), ALK mutations were detected in 12 of 276 samples (range of fraction of mutated allele: 0.811%–73.001%). Altogether, subclonal events with a mutated allele fraction below 20% were observed in 15/27 ALK-mutated samples. The presence of an ALK mutation was associated with poorer 5-year overall survival (OS: 75% vs. 57%, P = 0.0212 log-rank test), with a strong correlation between F1174 ALK mutations and MYCN amplification being observed. Conclusions: In this series, deep sequencing allows the detection of F1174 and R1275 ALK mutational events at diagnosis in 10% of cases, with subclonal events in more than half of these, which would have gone undetected by Sanger sequencing. These findings are of clinical importance given the potential role of ALK mutations in clonal evolution and relapse. These findings also demonstrate the importance of deep sequencing techniques for the identification of patients especially when considering targeted therapy. Clin Cancer Res; 21(21); 4913–21. ©2015 AACR. See related commentary by George, p. 4747